Association Between Non-O Blood Groups and Mortality in Pediatric Cerebral Malaria: A Systematic Review of Sequestration-Related Outcomes - Karina Agusta Putri (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION: Cerebral malaria (CM) remains a leading cause of pediatric mortality, driven by the sequestration of Plasmodium falciparum-infected erythrocytes (iRBCs). Host genetic factors, particularly the ABO blood group system, are implicated in disease severity. This review systematically evaluates the association between non-O blood groups (A, B, AB) and mortality in pediatric CM, with a specific focus on outcomes related to the pathophysiology of sequestration. METHODS: Following PRISMA guidelines, a systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted for observational studies published up to December 2025. Studies were included if they assessed pediatric populations with CM, compared outcomes between ABO blood groups, and reported on mortality or sequestration-related markers. Data were extracted for a primary outcome of all-cause mortality and seventeen secondary outcomes. The risk of bias in included non-randomized studies was assessed using the ROBINS-I (Risk Of Bias In Non-randomised Studies - of Interventions) tool. RESULTS: A total of 17 observational studies met the inclusion criteria. A consistent and significant association was found between non-O blood groups and increased risk of severe malaria and mortality. Compared to blood group O, non-O phenotypes were associated with higher odds of severe disease, with odds ratios (ORs) ranging from 1.27 to 6.28 in various comparisons. Mechanistically, non-O groups were linked to enhanced rosetting, a key driver of sequestration. This was accompanied by adverse biomarker profiles indicative of severe endothelial activation and dysfunction, including elevated von Willebrand factor (vWF) and Angiopoietin-2 (Ang-2), and decreased Angiopoietin-1 (Ang-1). Furthermore, non-O groups were associated with higher parasite densities in some studies, an increased incidence of severe anemia, and a greater risk of long-term neurological sequelae, completing the link between phenotype and clinical outcome. DISCUSSION: The synthesized evidence strongly supports a mechanistic link wherein A and B antigens on the surface of uninfected erythrocytes act as receptors for parasite ligands (PfEMP1) on iRBCs, promoting the formation of larger and more stable rosettes. This enhanced sequestration obstructs cerebral microvasculature, drives a cascade of endothelial dysfunction and inflammation, and culminates in the severe clinical manifestations and higher mortality observed in children with non-O blood groups. CONCLUSION: The non-O blood group is a significant and clinically relevant risk factor for mortality and adverse sequestration-related outcomes in pediatric cerebral malaria. ABO typing, a widely available and low-cost test, represents a valuable potential tool for early risk stratification and may inform clinical management decisions, such as transfusion strategies, in high-risk pediatric populations.